Paradoxical Hemiparesis from Cerebellopontine Angle Tumor: A Case Report - Gunawan, James; Gaharu, Maula Nuruddin (Faculty of Medicine Universitas Padjadjaran, 2023)
Objective: To report a vestibular schwannoma in the cerebellopontine angle presenting with paradoxical hemiparesis with the Kernohan-Woltman Notch Phenomenon (KWNP).Methods: A 31-year-old female presented to the neurology clinic at Bhayangkara Hospital TK. I R. Said Sukanto, Indonesia, on 29 November 2021 with loss of balance, hearing, vision, and weakness in her left arm and leg. On physical examination, the patient had reduced left arm and leg muscle strengths against resistance (MRC grade 4), face deviation to the left, abnormal finger-to-nose test, dysdiadochokinesia, and inability to perform tandem gait. She was admitted for a brain MRI but did not return to the hospital for re-evaluation and surgery. Results: The brain MRI showed a mass on the left side of the cerebellum with a size of 4.44x3.93x4.93 cm, suggesting vestibular schwannoma. The mass also caused the obliteration of the ventricle, causing hydrocephalus.Conclusion:KWNP is an unusual finding resulting in a paradoxical hemiparesis, a false-localizing neurologic sign. Physicians should recognize KWNP in patients with hemiparesis, especially in space-occupying lesions. Imaging studies can help localize the lesion to minimize misdiagnosis and optimize patient treatment.